Spatial and temporal assessment of sediment contamination in Sado estuary: a methodological approach - Nunes, L. (2009)
For better management of estuarine ecosystems their contamination assessment should be easily communicated to local managers and decision makers. The problem is the lack of available data and the search of methodologies to enable that assessment using only few data. The Sado estuary in Portugal is as good example of a site where human pressures and ecological values collide with each other and where the degree of metal and organic contamination has not been subject to an overall assessment, either in terms of spatial or temporal variability, in a way that managers can understand.